2016
DOI: 10.1002/2015jb012352
|View full text |Cite
|
Sign up to set email alerts
|

Deep crustal deformation of the Longmen Shan, eastern margin of the Tibetan Plateau, from seismic reflection and Finite Element modeling

Abstract: Rivaling the Himalaya in relief, the Longmen Shan is probably one of the most enigmatic mountain ranges in the world: high mountains reach more than 4000 m relief but without adjacent foreland subsidence and with only slow active convergence. What are geological and geodynamic processes that built the Longmen Shan? Coseismic deformation associated with the 2008 Wenchuan earthquake could hold clues to answer these questions. The primary features associated with the 2008 Wenchuan earthquake rupture have been nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 63 publications
6
59
0
Order By: Relevance
“…Despite the fact that the 3‐D image of the Moho shows a continuous surface at first order (Figure ), recent studies based on high‐resolution seismic reflection profiles have demonstrated that the Moho is discontinuous with prominent offsets (Guo et al, ; Robert et al, ; Z. J. Zhang et al, ). It is possible that some large, crustal‐scale thrust faults exist there (Feng et al, ; Lu et al, ). Therefore, we suggest that the “lower crustal flow” and the “brittle crustal shortening” models are not exclusive in building the eastern TP margin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that the 3‐D image of the Moho shows a continuous surface at first order (Figure ), recent studies based on high‐resolution seismic reflection profiles have demonstrated that the Moho is discontinuous with prominent offsets (Guo et al, ; Robert et al, ; Z. J. Zhang et al, ). It is possible that some large, crustal‐scale thrust faults exist there (Feng et al, ; Lu et al, ). Therefore, we suggest that the “lower crustal flow” and the “brittle crustal shortening” models are not exclusive in building the eastern TP margin.…”
Section: Discussionmentioning
confidence: 99%
“…Following the 2008 Wenchuan earthquake, numerous geophysical and geological surveys have provided constraints on the crustal and lithospheric structures of the eastern TP (Bai et al, ; Feng et al, ; Guo et al, ; Lei, Li, et al, ; Z. Liu et al, ; Z. Wang et al, , ; X. Wang, Li, et al, ; Wei et al, ; Z. J. Zhang et al, ). Most studies show that the Moho depth changes from ~60 km beneath the eastern TP to ~40 km beneath the SCB (Lei et al, ; H. Y. Li et al, ; Q. Y. Liu, van der Hilst, et al, ; C. Y. Wang et al, ; Xu & Song, ; P. Z. Zhang, ; Y. Q. Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the early aftershocks in the 24 hr following the mainshock with the seismic reflection profile along the CC' cross‐section region (Feng et al, ). Black and red lines are inferred dipping faults by Feng et al () and from profile CC' in this paper, respectively. Aftershocks (bold circles) are color‐coded by the occurrence times following the mainshock.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies over the last decade focused on subsurface structure, source process, and postseismic response of the 2008 Wenchuan earthquake by geological survey (Hubbard & Shaw, ; Ran et al, ; Xu et al, ; P. Z. Zhang et al, , ), seismology (Chen et al, , ; Deng et al, ; Feng et al, ; S. Li et al, ; Q. Liu et al, , , ; P. P. Zhao et al, ), geodesy (M. Huang et al, ; Shen et al, ; Q. Wang et al, ), and magnetotellurics (G. Z. M. Zhao et al, ). Different tectonic models have been proposed to explain the occurrence of the Wenchuan earthquake (Burchfiel et al, ; Feng et al, ; Hubbard & Shaw, ; Jia et al, ; Y. Q. Li et al, ; Shen et al, ; Q. Wang et al, ; Xu et al, ; P. Z. Zhang et al, ), but the geometry of seismogenic faults ruptured during the 2008 Wenchuan earthquake is still under debate (e.g., Xu et al, ; P. Z. Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This multilayer velocity model illustrates the nature of the subsurface velocity architecture, similar to the seismic velocity model of Wang et al [], and it enables the quantification of structural geometries more accurately than by simply using a constant velocity of 4600 m/s [ Jia et al ., ; Li et al ., ] (Figure ). In our model, the converted base of the shallow detachment layer in the LMS piedmont reaches an average depth of about 6 to 8 km, which is consistent with previous estimates from a deep seismic reflection profile using the common depth point stacking method [ Feng et al ., ] and depth conversions using a 2‐D velocity model [ Hubbard and Shaw , ; Hubbard et al ., ].…”
Section: Structures Of the Range Front Thrust Systemmentioning
confidence: 99%